Pengaruh Motivasi Belajar dan Perhatian Orang Tua terhadap Prestasi Belajar Matematika Siswa Kelas VIII SMPK - I Gusti Ayu Rarasanti; Ketut Sarjana; Sudi Prayitno; Sripatmi Sripatmi (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to determine the effect of learning motivation and parental attention on mathematics learning achievement of grade VIII students at SMPK Tunas Daud Mataram 2020/2021. This type of research is ex-post facto. The sample class was selected using a saturated sampling technique, obtained 34 students consisting of 2 classes. Data retrieval in this study was carried out by providing a questionnaire on learning motivation and parental attention and a number pattern test. Analysis of SPSS 21 program data, consisting of prerequisite tests and hypothesis testing. The prerequisite test on the data analysis used, namely the normality test of the results obtained on learning motivation, namely 0.245 and parental attention, namely 0.162 so that it is said that the data is normally distributed, the linearity test of the results obtained on learning motivation is 0.958 and parents' attention is 0.597 so that The data has a relationship with learning achievement and the multicollinearity test of the results obtained is 1.340, namely there is no relationship between independent variables. The contribution of learning motivation to mathematics learning achievement was 19.6% and parents' attention to mathematics learning achievement was 19.2%. The existence of a positive relationship between learning motivation and learning achievement and parents' attention to learning achievement is indicated by a positive correlation coefficient. A positive coefficient value indicates that the higher the motivation to learn and the attention of parents, the higher the student's learning achievement.